Planned conception in a hyper immunized rhesus-d negative mother by elective plasmapheresis - Ayesha, K; Babibullah, MM; Biswas, J; Begum, HA; Sultana, R (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S67-69 The abstract of this article is available on the PubMed website